Classification Of Cow Milk Using Artificial Neural Network Developed From The Spectral Data Of Single-and Three-detector Spectrophotometers - Shima Behkami; Sharifuddin M.Zain; Mehrdad Gholami; Mohd Fared Abdul Khir (Elsevier, 2024)
Food Chemistry Volume 294, 1 October 2019, Pages 309-315